2021
DOI: 10.3390/biomedicines9091188
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Smoothened-Dependent and -Independent Hedgehog Signaling Pathway in Tumorigenesis

Abstract: The Hedgehog (Hh)-glioma-associated oncogene homolog (GLI) signaling pathway is highly conserved among mammals, with crucial roles in regulating embryonic development as well as in cancer initiation and progression. The GLI transcription factors (GLI1, GLI2, and GLI3) are effectors of the Hh pathway and are regulated via Smoothened (SMO)-dependent and SMO-independent mechanisms. The SMO-dependent route involves the common Hh-PTCH-SMO axis, and mutations or transcriptional and epigenetic dysregulation at these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 260 publications
0
12
0
Order By: Relevance
“…The Discovery of PTCH1 gene mutation in people with Gorlin syndrome and sporadic forms of carcinoma basal cell carcinoma (CBC) has led to the importance of the hedgehog (HH) signalling pathway in human carcinogenesis [ 121 ]. Mutations in the PTCH1 gene or one of the components in the hedgehog (HH) signalling pathway is involved in the etiology and the development of some forms of cancers such as—medulloblastoma, breast cancer, colon cancer, pancreatic cancer, esophageal adenocarcinomas and in small cell lung cancer [ 122 ].…”
Section: Anti-cancer Effects Of Quercetin: Modulation Of Cancer Signa...mentioning
confidence: 99%
“…The Discovery of PTCH1 gene mutation in people with Gorlin syndrome and sporadic forms of carcinoma basal cell carcinoma (CBC) has led to the importance of the hedgehog (HH) signalling pathway in human carcinogenesis [ 121 ]. Mutations in the PTCH1 gene or one of the components in the hedgehog (HH) signalling pathway is involved in the etiology and the development of some forms of cancers such as—medulloblastoma, breast cancer, colon cancer, pancreatic cancer, esophageal adenocarcinomas and in small cell lung cancer [ 122 ].…”
Section: Anti-cancer Effects Of Quercetin: Modulation Of Cancer Signa...mentioning
confidence: 99%
“…The activity of Gli1 is regulated by Akt/p-S6K1 signaling. 78 ECM components laminin and fibronectin are also involved in the CSC self-renewal process. Chang et al demonstrated that laminin 511 helps maintain the breast cancer stemness properties by activating α6β1 integrin through the TAZdependent pathway.…”
Section: Extracellular Matrix Modification In Cancer Progressionmentioning
confidence: 99%
“…Dysregulation of Shh upshoots Gli transcription factors, and its target gene BMI1 helps develop brain tumors. , Gli expression is regulated by several types of FAK/Ras signaling. The activity of Gli1 is regulated by Akt/p-S6K1 signaling . ECM components laminin and fibronectin are also involved in the CSC self-renewal process.…”
Section: Extracellular Matrix Modification In Cancer Progressionmentioning
confidence: 99%
“…Unfortunately, toxicity and poor drug likeness are two major limitations of currently available GLI1 inhibitors. 4,6,16 Recently, glabrescione B (GlaB, Table 1) 17 was used by us as the initial scaffold for the generation of a five-feature pharmacophoric model that led to the identification of negative modulators of GLI1 belonging to the classes of thiophene and pyrazolo-pyrimidine small molecules that populated databases of commercially available compounds. 18 In addition, the same pharmacophore allowed the prioritization of several 8-hydroxyquinoline derivatives as putative GLI1 binders that are described here.…”
mentioning
confidence: 99%
“…Additional small molecules identified by virtual screening approaches were also described in recent years. Unfortunately, toxicity and poor drug likeness are two major limitations of currently available GLI1 inhibitors. ,, …”
mentioning
confidence: 99%